1999
DOI: 10.1086/314974
|View full text |Cite
|
Sign up to set email alerts
|

Polyspecific Self‐Reactive Antibodies in Individuals Infected with Human Immunodeficiency Virus Facilitate T Cell Deletion and Inhibit Costimulatory Accessory Cell Function

Abstract: Self-reactive polyspecific IgG antibodies (PSAs) arise in human immunodeficiency virus (HIV)-seropositive subjects before they develop AIDS. Self-reactive PSA levels correlate with the destruction of CD8 T cells in HIV-infected individuals and mediate the antibody-dependent cellular toxicity-based destruction of human T cells in tissue culture. PSAs react across the species barrier and bind to T cell antigens in mice. Such reactivity with mouse lymphocytes was not detected in normal human serum. Injection of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…25 The plasma IgG in HIV-1-infected subjects contains both anti-HIV Abs and other antibodies like PSA and autoantibodies. 38,43 In parallel, a loss of specific humoral immunity may occur as indicated by low levels of antibodies against several pathogens 26,27,44 and by the rapid loss of antigen-specific antibodies following immunization. [9][10][11]27 We measured antibodies to TT, a common vaccination antigen and to measles, a naturally acquired infection in our cohort, and found that the levels of IgG to both antigens were significantly reduced in HIV-1-infected individuals with low memory B cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The plasma IgG in HIV-1-infected subjects contains both anti-HIV Abs and other antibodies like PSA and autoantibodies. 38,43 In parallel, a loss of specific humoral immunity may occur as indicated by low levels of antibodies against several pathogens 26,27,44 and by the rapid loss of antigen-specific antibodies following immunization. [9][10][11]27 We measured antibodies to TT, a common vaccination antigen and to measles, a naturally acquired infection in our cohort, and found that the levels of IgG to both antigens were significantly reduced in HIV-1-infected individuals with low memory B cells.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of PSA have been detected in HIV-1 infection and these autoantibodies have been shown to bind lymphocytes and mediate T-cell death. 38 Human PSA from HIV-1-infected subjects showed a higher reactivity (defined as MFI) as compared with healthy subjects (11.8 [range, 4.6-53.9] vs 7.8 [range, 4.1-12.60; P Ͻ .01). In the HIV-1 population, the MFI of PSA was correlated to the plasma IgG (rho ϭ 0.547, P ϭ .001) and PSA reactivity was similar between HIV-1 NM subjects and HIV-1 LM subjects (15.9 [range, 10.3-23.8] vs 7.5 [range, 7-21.6]; P ϭ .226; Figure 6B).…”
Section: Polyclonal B-cell Activation and Naive/memory B Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…M⌽ that lack CD80 and CD86 expression are incapable of preventing the induction of anergy or apoptosis in conjugated T cells and act as negative immune regulators (42)(43)(44). In addition, M⌽ have the capacity to actively destroy T cells that they target for conjugate formation (44).…”
mentioning
confidence: 99%
“…Hallmarks of B cell abnormalities in HIV disease include hypergammaglobulinemia (2)(3)(4), increased expression of activation markers (5), increased levels of autoantibodies (6,7), increased risk of developing B cell lymphomas (8), and decreased responsiveness to in vivo vaccination and ex vivo stimulation (9,10). The range of defects in B cell responses includes both T cell-dependent and -independent pathways (1,11,12), suggesting that along with defects in CD4 ϩ T cell help, HIV infection causes intrinsic B cell defects.…”
mentioning
confidence: 99%